2016
DOI: 10.1371/journal.pone.0149905
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Ability of Anthropometric Indicators in Identifying Metabolic Syndrome in HIV Patients

Abstract: BackgroundHighly active antiretroviral therapy (HAART) can cause side effects in HIV patients, as the metabolic syndrome. Early identification of risk for development of cardiovascular diseases using available reliable and practical methods is fundamental. On this basis, the aim of this study was to compare the effectiveness of anthropometric indicators to identify metabolic syndrome in HIV patients on HAART.MethodsIt is a cross-sectional study. A number of 280 stable HIV patients were studied. It measured wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 46 publications
5
13
0
10
Order By: Relevance
“…Waist circumference also signi cantly associated with TC among female participants in ATV/r-treated group. In agreement with these results, a study done by Beraldo et al [30] reported signi cant association between waist circumference and TC levels.…”
Section: Discussionsupporting
confidence: 82%
“…Waist circumference also signi cantly associated with TC among female participants in ATV/r-treated group. In agreement with these results, a study done by Beraldo et al [30] reported signi cant association between waist circumference and TC levels.…”
Section: Discussionsupporting
confidence: 82%
“…The AC assesses the deposition of central fat in the abdominal region and abdominal obesity is a greater risk cardiovascular factor than overall obesity 29 . A study by Freitas and colleagues, the prevalence of abdominal lipodystrophy among women also reached the 80% range, double the prevalence of males, corroborating the present study 27 .…”
Section: Rev Bras Epidemiol Jul-set 2017; 20(3): 526-536mentioning
confidence: 99%
“…However, the authors encourage the routine use of indicators such as WC, since they have a better predictive capacity for cardiometabolic risk in patients with HIV infection (k = 0.20, p= 0.001) 34 . Beraldo et al 35 also reinforce the use of WC in the evaluation of PLH, since this parameter evaluates fat deposition in the abdominal region, because abdominal visceral obesity is a more serious cardiovascular risk factor than general obesity, and is usually evaluated by IMC 35 .…”
Section: Discussionmentioning
confidence: 99%